The genome diversity and karyotype evolution of mammals - Graphodatsky, Alexander S (BioMed Central, 2011)
The past decade has witnessed an explosion of genome sequencing and mapping in evolutionary diverse species. While full genome sequencing of mammals is rapidly progressing, the ability to assemble and align orthologous whole chromosome regions from more than a few species is still not possible. The intense focus on building of comparative maps for companion (dog and cat), laboratory (mice and rat) and agricultural (cattle, pig, and horse) animals has traditionally been used as a means to understand the underlying basis of disease-related or economically important phenotypes. However, these maps also provide an unprecedented opportunity to use multispecies analysis as a tool for inferring karyotype evolution. Comparative chromosome painting and related techniques are now considered to be the most powerful approaches in comparative genome studies. Homologies can be identified with high accuracy using molecularly defined DNA probes for fluorescence in situ hybridization (FISH) on chromosomes of different species. Chromosome painting data are now available for members of nearly all mammalian orders. In most orders, there are species with rates of chromosome evolution that can be considered as 'default' rates. The number of rearrangements that have become fixed in evolutionary history seems comparatively low, bearing in mind the 180 million years of the mammalian radiation. Comparative chromosome maps record the history of karyotype changes that have occurred during evolution. The aim of this review is to provide an overview of these recent advances in our endeavor to decipher the karyotype evolution of mammals by integrating the published results together with some of our latest unpublished results.